Indonesian EFL teachers - Nadjib, Nurfadilah; Triastuti, Anita (Journal on English as a Foreign Language, 2023)
Many studies indicated a genre-based approach (GBA) as an effective method in English foreign language (EFL) teaching and GBA is also integrated into the English teaching curriculum. However, EFL teachers' portraits of GBA use in teaching practices are little understood. This study aimed to explore EFL teachers' perceptions of GBA, the implementation of GBA in EFL classrooms, and the challenges EFL teachers face when implementing GBA. This case study research involved 28 English teachers from different public high schools in Yogyakarta, Indonesia. The data were obtained from the teachers